Assessing unit readiness : case study of an Air Force mobility wing - Thaler, David E.; Dahlman, Carl J., 1950-; Rand eBooks (Santa Monica, CA : RAND, 2002)
The U.S. Air Force has recently confronted a multiplicity of challenges in its efforts to maintain military readiness in the face of constrained resources and increasingly demanding contingency requirements. This briefing explores the nature and extent of such challenges within the air mobility community by focusing on the 60th Air Mobility Wing (AMW) at Travis Air Force Base, California. Drawing from extensive research as well as from detailed surveys of unit personnel, the briefing concludes that the 60th AMW has in fact faced a variety of stringent and often-competing challenges, including dramatic fluctuations in the demand for airlift and tanker support; a decline in experience mix brought about by the loss of experienced pilots and maintainers to the civilian sector; a consequent need for the training of new and inexperienced personnel; and a maintenance workload burdened by frequent shortages of parts and "out-of-hide" responsibilities. The events of September 11 eased many of these challenges, but this is seen as only a temporary respite. The report also finds that senior personnel have borne the brunt of these challenges by having to sustain high levels of productivity while simultaneously ensuring that more junior personnel are adequately trained. The authors conclude that the problems facing the 60th AMW would appear to typify those of Air Force mobility wings in general. While these problems do not prevent the wing from meeting its short-term operational demands, the situation cannot be sustained over the longer term.
"Project Air Force."
Includes bibliographical references (p. 55).
Also available on the internet via WWW in PDF format.
Description based on print version record.
Keywords: United States. -- Air Force -- Operational readiness -- Case studies; Military readiness -- Case studies; Operational readiness (Military science); Electronic books